Capital and ideology [compact disc, unabridged] - Piketty, Thomas, 1971- (Harvard University Press, 2020)
Thomas Piketty exposes the ideas that have sustained inequality for the past millennium, reveals why the shallow politics of right and left are failing us today, and outlines the structure of a fairer economic system.